PERKEMBANGAN TEKNOLOGI BATUBARA BERSIH BERWAWASAN LINGKUNGAN - Suwarna, Endang (Jurnal Teknologi Lingkungan, 2011)
Coal has a very important role to meet energy demand in Indonesia, however, it is also the dirtiest fuel among the fossil fuels. As coal utilization continues to increase, pollutants and greenhouse gases emissions from the coal utilization also increase, that would lead to environmental problems. Therefore, development of clean coal technologies for reducing those emissions from coal utilization needs to be considered. The technologies areintended to reduce the policy conflict between continuing coal utilization and protecting environment potential by improving the effectiveness of control technologies and reducing their costs. In addition, the technologies have higher efficiency that would impact on conserving fuels that lead to reducing costs and extension of coal reserve availability.